PENGARUH KREDIT PERTANIAN TERHADAP KESEJAHTERAAN PETANI KELAPA SAWIT DI KABUPATEN LABUHAN BATU UTARA - Mardiana Lumbanraja (Departemen Ekonomi Pembangunan USU, 2013)
The role of agricultural sector would be optimal if it’s supported by an integrated system of planning, sustainable, and balanced with the provision of adequate budget such as capital. Issue of capital is a problem who faced by farmers, although many farmers who have the ability to improve their crops if farmers have sufficient capital, then their will not be able to developing their farm. So, to solve the capital shortage, farmers would apply for loans to financial institutions both formal and informal. However, at this time growth of credit has increased especially credit agricultural sector, which is programmed by the government to improve the rural economy that agricultural area.Agricultural credit has a very important role in developing agricultural development to obtain a greater yield. If production has increased, then will increase farmers' income also for farmers welfare. Therefore, researcher has researched by using research methods by distribution 30 questionnaires to oil palm farmers in the district of North Labuhanbatu. The research variables are equity (X1), capital credits (X2), and land (X3) using multiple linear regression analysis. Based on the analysis, can be concluded that the application of agricultural credit in the District of North Labuhanbatu already be applicable to well, but not entirely for the management of oil palm agriculture. With a confidence level of 95% result test value 0.598 coefficient of determination can be concluded that the analysis of the influence of agricultural credit to farmers welfare to oil palm with research variables can explain the variation in the level of revenue of 59.8% and the remaining 40.2% is explained by other variables not included in the model estimation.Keywords: Agricultural Credit, Income, Welfare